Inducible Costimulator Expressing T Cells Promote Parasitic Growth During Blood Stage Plasmodium berghei ANKA Infection - Jogdand, Gajendra M.; Sengupta, Soumya; Bhattacharya, Gargee; Singh, Santosh Kumar; Barik, Prakash Kumar; Devadas, Satish (Frontiers in Immunology, 2018)
The lethality of blood stage P.berghei ANKA (PbA) infection is associated with the expression of T-bet and production of cytokine IFN-γ. Expression of Inducible costimulator (ICOS) and its downstream signaling has been shown to play a critical role in the T-bet expression and IFN-γ production. Although earlier studies have examined the role of ICOS in the control of acute blood-stage infection of P. chabaudi chabaudi AS (a non-lethal model of malaria infection), its significance in the lethal blood-stage of PbA infection remains unclear. Thus, to address the seminal role of ICOS in lethal blood-stage of PbA infection, we treated PbA infected mice with anti-ICOS antibody and observed that these mice survived longer than their infected counterparts with significantly lower parasitemia. Anti-ICOS treatment notably depleted ICOS expressing CD4+ and CD8+ T cells with a concurrent reduction in plasma IFN-γ which strongly indicated that ICOS expressing T cells are major IFN-γ producers. Interestingly, we observed that while ICOS expressing CD4+ and CD8+ T cells produced IFN-γ, ICOS-CD8+ T cells were also found to be producers of IFN-γ. However, we report that ICOS+CD8+ T cells were higher producers of IFN-γ than ICOS-CD8+ T cells. Moreover, correlation of ICOS expression with IFN-γ production in ICOS+IFN-γ+ T cell population (CD4+ and CD8+ T cells) suggested that ICOS and IFN-γ could positively regulate each other. Further, master transcription factor T-bet importantly involved in regulating IFN-γ production, was also found to be expressed by ICOS expressing CD4+ and CD8+ T cells during PbA infection. As noted above with IFN-γ and ICOS, a positive correlation of expression of ICOS with the transcription factor T-bet suggested that both of them could regulate each other. Taken together, our results depicted the importance of ICOS expressing CD4+ and CD8+ T cells in malaria parasite growth and lethality through IFN-γ production and T-bet expression.